RUBCN/rubicon and EGFR regulate lysosomal degradative processes in the retinal pigment epithelium (RPE) of the eye. Issue 12 (2nd December 2017) - Muniz-Feliciano, Luis; Doggett, Teresa A.; Zhou, Zhenqing; Ferguson, Thomas A.
ABSTRACT: Macroautophagy/autophagy is an intracellular stress survival and recycling system whereas phagocytosis internalizes material from the extracellular milieu; yet, both pathways utilize lysosomes for cargo degradation. Whereas autophagy occurs in all cells, phagocytosis is performed by cell types such as macrophages and the retinal pigment epithelial (RPE) cells of the eye where it is supported by the noncanonical autophagy process termed LC3-associated phagocytosis (LAP). Autophagy and LAP are distinct pathways that use many of the same mediators and must compete for cellular resources, suggesting that cells may regulate both processes under homeostatic and stress conditions. Our data reveal that RPE cells promote LAP through the expression of RUBCN/Rubicon (RUN domain and cysteine-rich domain containing Beclin 1-interacting protein) and suppress autophagy through the activation of EGFR (epidermal growth factor receptor). In the morning when photoreceptor outer segments (POS) phagocytosis and LAP are highest, RUBCN expression is increased. At the same time, outer segment phagocytosis activates the EGFR resulting in MTOR (mechanistic target of rapamycin [serine/threonine kinase]) stimulation, the accumulation of SQSTM1/p62, and the phosphorylation of BECN1 (Beclin 1, autophagy related) on an inhibitory residue thereby suppressing autophagy. Silencing Rubcn, preventing EGFR activity or directly inducing autophagy in RPE cells by starvation inhibits phagocytic degradation of POS. Thus, RPE cells regulate lysosomal pathways during the critical period of POS phagocytosis to support retinal homeostasis.